Development and evaluation of a rapid RPA/CRISPR-based detection of Francisella tularensis - Xu, Jian-Hao; Kang, Lin; Yuan, Bing; Feng, Zi-Han; Li, Shi-Qing; Wang, Jing; Wang, Ya-Ru; Xin, Wen-Wen; Gao, Shan; Li, Jia-Xin; Sun, Yan-Song; Wang, Jing-Lin; et al. (Frontiers in Microbiology, 2022)
Francisella tularensis is a dangerous pathogen that causes an extremely contagious zoonosis in humans named tularemia. Given its low-dose morbidity, the potential to be fatal, and aerosol spread, it is regarded as a severe threat to public health. The US Centers for Disease Control and Prevention (CDC) has classified it as a category A potential agent for bioterrorism and a Tier 1 Select Agent. Herein, we combined recombinase polymerase amplification (RPA) with CRISPR/Cas12a system to select the F. tularensis target gene (TUL4), creating a two-pronged rapid and ultrasensitive diagnostic method for detecting F. tularensis. The real-time RPA (RT-RPA) assay detected F. tularensis within 10 min at a sensitivity of 5 copies/reaction, F. tularensis genomic DNA of 5 fg, and F. tularensis of 2 × 102 CFU/ml; the RPA-CRISPR/Cas12a assay detects F. tularensis within 40 min at a sensitivity of 0.5 copies/reaction, F. tularensis genomic DNA of 1 fg, and F. tularensis of 2 CFU/ml. Furthermore, the evaluation of specificity showed that both assays were highly specific to F. tularensis. More importantly, in a test of prepared simulated blood and sewage samples, the RT-RPA assay results were consistent with RT-PCR assay results, and the RPA-CRISPR/Cas12a assay could detect a minute amount of F. tularensis genomic DNA (2.5 fg). There was no nonspecific detection with blood samples and sewage samples, giving the tests a high practical application value. For example, in on-site and epidemic areas, the RT-RPA was used for rapid screening and the RPA-CRISPR/Cas12a assay was used for more accurate diagnosis.